(untitled) (Journal of the College of Basic Education, 2022)
The research has several chapters. The first chapter contains the research problem, its importance, its objectives and its limitations regarding The second chapter dealt with the theoretical framework, which included the following topics: The first topic: a historical overview of the origin and development of the art of barbutin pottery, in addition to the topic The second: who talked about the decorative components of the Barbutin pottery in Iraq. As for the third topic: He talked about the plastic elements in the Barbotene pottery, in addition to the four topic: which included the organization morphology in the barbutene pottery The third chapter was a chapter on the procedures and the analysis of the sample that concerned the pottery of barbutin in The city of Nineveh as a sample for research in the following